Preserving Gambang Semarang Music Through The Process of Enculturation in The Society - Raharjo, Eko; Soesanto, Soesanto; Rohidi, Tjetjep Rohendi; Utomo, Udi (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2021)
This study was devoted to investigating the preservation of gambang Semarang music through the enculturation process comprehensively. Two basic strategies were employed in examining research problems: using theoretical approaches in traditional music, preservation, and enculturation and a qualitative approach. Further, the target and site comprised gambang Semarang music preservation through the enculturation process among Semarang people. The data were collected from observation, interviews, documentation, and library research. Data validity applied source, time, theory, and researcher triangulation. The collected data and information were then analyzed inductively by relying on an interactive analysis model with the following steps: data reduction, display, and verification. It was suggested that the enculturation process of gambang Semarang music within three generations in the nang nok gambang Semarang group served as the activity of cultural awareness of society, artists, and performers. It was to carry out the enculturation process towards young generations, even children, as the future generations. The approaches to the teaching and learning process were modeling, conditioning, and internalization. Such an enculturation process was proven to function effectively as the cultural mechanism and enculturation model in preserving gambang Semarang music as the cultural identity of Semarangan.